THE EFFECTIVENESS OF REPRODUCTIVE HEALTH EDUCATION WITH LEAFLETS ON ADOLESCENT KNOWLEDGE ABOUT EARLY MARRIAGE AT THE YOUTH POSYANDU - Siti Marhamah; Anik Sri Purwanti (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2026)
Background: Early marriage is a major public health concern that affects adolescents’ physical, psychological, and social well-being. Limited knowledge about reproductive health often leads to early marriage, unwanted pregnancies, and related complications. Providing accurate and accessible information through educational interventions is crucial to empower adolescents to make informed decisions and delay marriage. Leaflets are a practical and cost-effective medium to deliver reproductive health education, especially in community-based settings such as Youth Posyandu. Objective: This study aimed to determine the effectiveness of reproductive health education delivered through leaflets in improving adolescents’ knowledge about early marriage at the Youth Posyandu. Methods: This research employed a quantitative analytical design with a pretest-posttest approach using a cross-sectional design. The sample consisted of 30 adolescents selected using a total sampling technique. Data were collected using structured questionnaires measuring knowledge about reproductive health and early marriage before and after the leaflet-based education. The Wilcoxon signed-rank test was used to analyze the effectiveness of the intervention. Results: The results indicated that all 30 adolescents demonstrated improved knowledge after receiving reproductive health education through leaflets. The Wilcoxon signed-rank test showed a p-value of 0.000, indicating a statistically significant increase in knowledge regarding early marriage among the participants. Conclusion: Reproductive health education using leaflets is effective in improving adolescents’ knowledge about early marriage. This intervention can be recommended as an accessible and practical strategy to prevent early marriage in adolescent populations through Youth Posyandu programs.